Molecular detection of feline leukemia virus (FeLV) in clinically ill local cats - Mummoorthy, Kunambiga (2017)
Feline leukemia virus (FeLV) belongs under the genus Gammaretrovirus and is associated with a wide range of clinical signs worldwide. Sofar, the first and only molecular characterization of local FeLV isolates performed in 2014 revealed that local isolates to be closely related to UK isolate. Due to limited coverage of the study and the nature of the virus that typically integrates the DNA into the host genome and undergoes mutation, study on the current status of FeLV infection is necessary. Therefore, this study aim to detect FeLV antigen in clinically ill cats by RT-PCR and to compare the currently identified variant similarity with previous related virus isolates from Malaysia and other geographical distribution. By using convenience sampling method, plasma and saliva were collected from 15 clinically ill cats and 5 healthy cats from Gasing Veterinary Hospital. Viral nucleic acid was extracted and subjected to One-Step RT PCR with specific primer targeting the highly conserved U3LTR and partial gag regions. Two cats were tested positive for the antigen from the clinically ill group. Partial nucleotide sequencing and phylogenetic analysis revealed that the current variant are found to be 93-99% homologous to the previous Malaysian isolates and is still closely related to UK isolate. Interestingly, they were also found to be closely related to isolates from Japan. In conclusion, this study highlights the possibilities of evolutionary relations between FeLV from Malaysia with FeLV of UK and Japan.